Ladylene crosslinking comonomer, degradable PDCPD thermosetting material, and preparation method and application of degradable PDCPD thermosetting material

By using crosslinking agent with bisclene structure and thermally driven self-propagation technology of dicyclopentadiene, the problems of difficulty in degrading and recycling of PDCPD materials and the risk of chemical stimulation degradation and resolution are solved, and the controllable degradation and performance improvement of PDCPD materials are achieved.

CN119462729APending Publication Date: 2025-02-18ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411603446.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The crosslinking network structure of existing PDCPD materials makes it difficult to degrade and recover, and there is a risk of chemical stimulation degradation, affecting the performance of the material.

Method used

The crosslinking agent with a bisclene structure is used to achieve controllable degradation of PDCPD materials through statistical copolymerization of the thermally driven self-propagation technology of the tilene-based crosslinking comonomer and dicyclopentadiene.

Benefits of technology

It improves the degree of cross-linking of PDCPD materials, enhances its mechanical properties and thermal stability, and at the same time achieves controllable degradation under chemical stimulation, meeting the dual requirements of material stability and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462729A_ABST
    Figure CN119462729A_ABST
Patent Text Reader

Abstract

The invention provides a laddecenyl cross-linked comonomer and a preparation method thereof. The structural formula of the laddecenyl cross-linked comonomer is as follows: # imgabs0 #. The invention also provides a degradable PDCPD thermosetting material based on the laddecenyl cross-linked comonomer and a preparation method of the degradable PDCPD thermosetting material. The degradable PDCPD thermosetting material can be applied to unmanned aerial vehicles, unmanned ships and unmanned ship shell materials. The laddecenyl cross-linked comonomer is a cross-linking agent with a double-laddecenyl structure, so that the cross-linking degree of PDCPD is increased, the impact strength, tensile strength and the like of the material are improved, and the mechanical property and thermal stability of the material are enhanced while the PDCPD material is endowed with degradation performance; meanwhile, a force-sensitive element cyclobutane in the monomer keeps the chemical stability of the PDCPD thermosetting material, and controllable degradation of the PDCPD material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmentally friendly polymer materials, and in particular to a ladder-based cross-linked comonomer, a degradable PDCPD thermosetting material, and a preparation method and application thereof. Background Art

[0002] Due to its excellent thermal stability, mechanical properties and corrosion resistance, PDCPD is widely used in aerospace, transportation, electronics / electrical and military fields. However, the cross-linked network structure of PDCPD makes it difficult to degrade and recycle. In addition, with the continuous expansion of PDCPD's application fields and the increase in consumption year by year, the environmental pollution and ecological harm caused by waste PDCPD are becoming more and more serious.

[0003] At present, the degradability of polymers is usually achieved by introducing moieties that can break bonds under certain conditions, such as esters, imines, ether bonds, disulfide bonds, acetals and silyl ethers, such as Chinese patent CN 115028760A, which invented a degradable polystyrene based on nitrobenzyl disulfide and pyridinium ester block macromolecular chain transfer agents. These degradable moieties can give polymers degradability, but at the same time, the degradable moieties may also be triggered by the environment, making the polymer unstable during processing, storage and use, resulting in a decrease in molecular weight, leading to deterioration of the mechanical properties and physical properties of the material. Existing methods for improving the thermal stability of polymers include improving the elasticity and crystallinity of polymers, adding stabilizers, and blending with non-degradable polymers, but these methods lack versatility and may be costly. With the growing demand for degradable polymers, better strategies are needed to improve the stability of polymers while still maintaining degradability.

[0004] Chinese invention patent CN 117362266A provides a force-sensitive acetal monomer containing ladder ene, which randomly introduces the acetal monomer structure containing ladder ene structure into the polydicyclopentadiene molecular chain through heat-driven spreading copolymerization technology, giving the copolymer material the ability to respond to ring opening under mechanical force induction and chemical stimulation. However, the monomer only contains one ladder ene unit, the cross-linking degree of the material is low, and the mechanical properties are reduced. Chinese patent CN 117343235 A provides a monomer containing a trifunctional silyl ether unit. The COSiO3 copolymer monomer makes the polydicyclopentadiene material have good degradation performance, and at the same time has excellent strength and thermal stability. The introduction of the silyl ether structure gives the material good toughness and enhances the mechanical properties of the material. However, the degradable unit in this monomer is directly added to the main chain, and there is also a risk of degradation under chemical stimulation, which affects the material performance.

[0005] Domestic research in this field is in its infancy and relevant patent information is relatively scarce. Therefore, the present invention will provide ideas and directions for the controllable degradation and recycling of thermosetting polymer materials. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a ladder-based cross-linked copolymer monomer, a degradable PDCPD thermosetting material, and a preparation method and application thereof; the monomer of the present invention is a cross-linking agent of a double ladder-based structure, which will increase the cross-linking degree of PDCPD, thereby improving the impact strength, tensile strength, etc. of the material, and while giving the PDCPD material degradation performance, it also enhances the mechanical properties and thermal stability of the material; at the same time, the design of the force-sensitive unit cyclobutane in the monomer requires that the chemically stimulated degradation unit appear in the polymer main chain under the action of mechanical force, thereby maintaining the chemical stability of the PDCPD thermosetting material itself and realizing the controllable degradation of the PDCPD material; the degradable monomer and dicyclopentadiene can be statistically copolymerized by heat-driven self-propagating technology, thereby realizing the controllable degradation of the PDCPD thermosetting material under mechanical force induction and chemical stimulation.

[0007] The present invention adopts the following technical solutions to solve the above technical problems:

[0008] A ladder olefin cross-linking comonomer, which is a ladder olefin cross-linking comonomer containing a silyl ether unit and a force-sensitive unit, and has a structural formula as follows:

[0009] As shown in formula 1:

[0010]

[0011] In the formula, R1 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 One or more of the sulfur heterocyclic groups; preferably, R1 is selected from C 1-6 Alkyl, halo; further preferably, R1 is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, fluorine, chlorine, bromine, iodine; most preferably, R1 is selected from methyl, chlorine.

[0012] R2 is selected from one or more of a direct bond, methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, methyleneoxycarbonyl, ethyleneoxycarbonyl, methylenyl, methyleneoxy, ethyleneoxy, and propyleneoxy; preferably, R2 is selected from a direct bond, methylene, and 1,2-ethylene.

[0013] R3 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 Preferably, R3 is selected from C 1-6 Alkyl, halo; further preferably, R3 is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, fluorine, chlorine, bromine, iodine; most preferably, R3 is selected from methyl, chlorine.

[0014] A method for preparing the above-mentioned ladder-based cross-linked comonomer is synthesized by reacting ladder-based diol and dichlorosilane, and the reaction equation is shown in Formula 2:

[0015]

[0016] First, dissolve the ladderene diol and the catalyst in an organic solvent, and lower the temperature to below 0°C. Add dichlorosilane dropwise to the above solution, and react and stir at 0-100°C for 4-48 hours. After the reaction is completed, wash, separate, and dry to obtain a ladderene-based cross-linked copolymer containing a silyl ether unit and a force-sensitive unit.

[0017] As one of the preferred embodiments of the present invention, the organic solvent is one or more of benzene, toluene, xylene, isopropyl benzene, isopentane, n-pentane, cyclopentane, n-hexane, cyclohexane, cyclohexanone, toluene cyclohexanone, methylcyclohexane, heptane, n-octane, isooctane, dichloromethane, 1,2-dichloroethane, chloroform, trichloroethane, carbon tetrachloride, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl formate, isobutyl acetate, propyl acetate, ether, petroleum ether, isopropyl ether, methyl tert-butyl ether, anisole, tributyl methyl ether, propylene oxide, dioxane, tetrahydrofuran, dioxane, methyl ethyl ketone, acetone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methanol, ethanol, and isopropanol.

[0018] As one of the preferred embodiments of the present invention, the catalyst is one of imidazole, 1-methylimidazole, 2-methylimidazole, benzimidazole, monoethanolamine, diethanolamine, diisopropanolamine, N-methyldiethanolamine, triethylamine, triethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, pyridine, 4-pyrrolidinopyridine, 4-N,N-dimethylpyridine, and 4-dimethylaminopyridine.

[0019] A degradable PDCPD thermosetting material, based on the above-mentioned ladder olefin cross-linking comonomer, has a structural formula as shown in Formula 3:

[0020]

[0021] Wherein, x, y, z, m, n, and p are all integers between 5 and 100;

[0022] At the same time, R1 is selected from hydrogen atoms, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 One or more of the sulfur heterocyclic groups; preferably, R1 is selected from C 1-6 Alkyl, halo; further preferably, R1 is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, fluorine, chlorine, bromine, iodine; most preferably, R1 is selected from methyl, chlorine.

[0023] R2 is selected from one or more of a direct bond, methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, methyleneoxycarbonyl, ethyleneoxycarbonyl, methylenyl, methyleneoxy, ethyleneoxy, and propyleneoxy; preferably, R2 is selected from a direct bond, methylene, and 1,2-ethylene.

[0024] R3 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 Preferably, R3 is selected from C 1-6 Alkyl, halo; further preferably, R3 is selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, fluorine, chlorine, bromine, iodine; most preferably, R3 is selected from methyl, chlorine.

[0025] As one of the preferred embodiments of the present invention, the preparation of the degradable PDCPD thermosetting material includes the following raw materials in parts by weight:

[0026]

[0027] Further preferably, the preparation of the degradable PDCPD thermosetting material comprises the following raw materials in parts by weight:

[0028]

[0029] A method for preparing the above-mentioned degradable PDCPD thermosetting material is synthesized by front-end ring-opening metathesis polymerization of dicyclopentadiene and ladder-based cross-linked comonomers under the action of a ruthenium-based catalyst and a phosphate inhibitor.

[0030] A method for degrading the above-mentioned degradable PDCPD thermosetting material, comprising the following steps:

[0031] (1) Activate the degradation properties of PDCPD thermosetting materials under mechanical force;

[0032] (2) Immersing the sample prepared in step (1) in a mixture of an acid solution or an alkaline solution and a solvent at room temperature or under heating conditions; degrading the PDCPD thermosetting material into soluble oligomer fragments under stirring conditions.

[0033] As one of the preferred embodiments of the present invention, the mechanical force is in the form of one or more of ultrasound, mechanical vibration, ball milling, grinding, impact, calendering, crushing, shearing, stretching, torsion, and bending.

[0034] As one of the preferred embodiments of the present invention, the acid in the acid solution is one or more of hydrochloric acid, hydrobromic acid, hydrofluoric acid, hydrocyanic acid, hydrosulfuric acid, nitric acid, sulfuric acid, sulfurous acid, acetic acid, acetic acid, trifluoroacetic acid, trichloroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, lactic acid, formic acid, propionic acid, citric acid, sulfurous acid, phosphoric acid, benzoic acid, maleic acid, phthalic acid, hypochlorous acid, chloric acid, chlorous acid, and perchloric acid;

[0035] The alkali in the alkali solution is one or more of tetrabutylammonium fluoride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetrabutylammonium chloride, tetramethylammonium fluoride, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium iodide, tetraethylammonium fluoride, tetraethylammonium chloride, tetraethylammonium bromide, tetraethylammonium iodide, tetrapropylammonium fluoride, tetrapropylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium iodide, tributylmethylammonium fluoride, and tetraoctylammonium fluoride;

[0036] The solvent is one or more of water, n-pentane, isopentane, cyclopentane, hexane, cyclohexane, heptane, benzene, toluene, xylene, chlorobenzene, isopropylbenzene, dichloromethane, 1,2-dichloroethane, chloroform, trichloroethane, carbon tetrachloride, methanol, ethanol, ethylene glycol, propanol, isopropanol, butanol, isobutyl alcohol, tert-butyl alcohol, amyl alcohol, benzyl alcohol, ethyl acetate, ethyl formate, isobutyl acetate, methyl acetate, ethyl ether, petroleum ether, isopropyl ether, methyl tert-butyl ether, tetrahydrofuran, dioxane, methyl ethyl ketone, acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.

[0037] As one of the preferred embodiments of the present invention, the molar concentration of the acid or base in the mixed solution of the acid solution or the base solution and the solvent is 0.01 to 100 mol / L, preferably 0.1 mol / L.

[0038] As one of the preferred embodiments of the present invention, the heating conditions are: heating temperature 0°C to 100°C, and heating time 1 to 100 hours.

[0039] An application of the above-mentioned degradable PDCPD thermosetting material in the hull materials of unmanned aerial vehicles, unmanned boats and unmanned ships.

[0040] The advantages of the present invention compared to the prior art are:

[0041] (1) The ladder-based cross-linked copolymer containing silyl ether motifs and force-sensitive motifs of the present invention is statistically copolymerized with dicyclopentadiene monomer by heat-driven self-propagating technology to achieve controllable degradation of PDCPD thermosetting materials under mechanical force induction and chemical stimulation;

[0042] (2) The monomer of the present invention contains two ladder ene structures, which will increase the cross-linking degree of the molecular chain, thereby improving the mechanical properties of the material such as tensile strength and impact strength, as well as high temperature resistance; and the increase in the content of chemically stimuli-degradable silyl ether units in the monomer will improve the degradation performance of the material; therefore, the present invention improves the degradation performance of the PDCPD material while increasing the various physical and mechanical properties of the material, so that the PDCPD material can meet the basic market demand while achieving recycling;

[0043] (3) The degradable PDCPD thermosetting material of the present invention can be completely degraded into soluble fragments under the action of mechanical force and chemical stimulation. The tensile strength and initial decomposition temperature of the material are 65MPa and 453°C, respectively, and the glass transition temperature is 232°C. It has excellent strength and thermal stability while having degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a synthetic flow chart of the ladder-based cross-linked comonomer A containing a silyl ether moiety and a force-sensitive moiety in Example 1;

[0045] Figure 2 is the crosslinking copolymerization monomer A containing silyl ether unit and force sensitive unit in Example 1 1 H-NMR spectrum;

[0046] Figure 3 is a synthetic flow chart of the ladder-based cross-linked comonomer B containing a silyl ether moiety and a force-sensitive moiety in Example 10;

[0047] Figure 4 is the crosslinking copolymerization monomer B containing silyl ether unit and force sensitive unit in Example 10 1 H-NMR spectrum;

[0048] Figure 5 is a synthetic flow chart of the ladder-based cross-linked comonomer C containing a silyl ether moiety and a force-sensitive moiety in Example 11;

[0049] Figure 6 is the crosslinking copolymerization monomer C of ladder olefin containing silicon ether unit and force sensitive unit in Example 11 1 H-NMR spectrum;

[0050] Figure 7 1 is a synthetic flow chart of the monomer D containing a silyl ether moiety, a cyclobutene moiety, and an anergy-sensitive moiety in Example 1;

[0051] Figure 8 The monomer D containing silyl ether moiety, cyclobutene and anergy-sensitive moiety in Example 7 is 1 H-NMR spectrum;

[0052] Fig. 9 This is a synthetic flow chart of the monomer G containing a silyl ether moiety, an insensitive moiety and cyclobutene in Comparative Example 10;

[0053] Fig.10 The monomer G containing silyl ether moiety, anhydrous sensitization moiety and cyclobutene in Comparative Example 10 is 1 H-NMR spectrum. DETAILED DESCRIPTION

[0054] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0055] About the raw materials used in the following examples and comparative examples:

[0056] Dicyclopentadiene: purchased directly from Sigma-Aldrich.

[0057] Monomers A, B, and C: ladder-based cross-linked copolymers containing silicon ether units and force-sensitive units synthesized by the present invention, and the structural formulas are detailed in Examples 1, 10, and 11; Monomers D and G: functional monomers designed and synthesized by the present invention, and the structural formulas are detailed in Comparative Examples 7 and 10; the chemical reagents and organic solvents required for the synthesis are preferably products of Shanghai Aladdin Biochemical Technology Co., Ltd.

[0058] Monomer E, F: tricyclo[4.2.0.02,5]octa-3,7-diene and 1,5-cyclooctadiene, respectively, preferably from Sigma-Aldrich.

[0059] Catalyst (PDCPD thermosetting material synthesis): Grubbs second generation catalyst.

[0060] Inhibitor (PDCPD Thermoset Synthesis): Tributyl phosphate is preferably from Sigma-Aldrich.

[0061] Other production raw materials and additives are commonly used commercial industrial products;

[0062] All necessary reagents are available from commercial sources.

[0063] Table 1 Raw materials and dosage used in each example

[0064]

[0065]

[0066] Table 2 Raw materials and dosage used in each comparative example

[0067]

[0068] Example 1

[0069] A polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of the present embodiment includes the following raw materials in parts by weight: 96.82 parts of dicyclopentadiene, 3 parts of ladder-based cross-linked copolymer monomer A containing silyl ether units and force-sensitive units, 0.15 parts of a catalyst, and 0.03 parts of an inhibitor (as shown in Table 1).

[0070] Among them, the structure of the ladder-based cross-linked comonomer A containing a silyl ether unit and a force-sensitive unit is shown in Formula 4:

[0071]

[0072] Monomer A in this example (synthetic route diagram see Figure 1 ) preparation:

[0073] (1) In a three-necked flask containing 200 ml of dichloromethane, 0.2 mol (28.036 g) of bicyclo[2.2.0]hex-5-ene-2,3-diethanol and 0.22 mol (14.982 g) of imidazole were added and stirred; then 0.1 mol (25.611 g) of 1,2-bis(methyldichlorosilyl)ethane was dissolved in 150 ml of dichloromethane, and the mixture was added dropwise to the three-necked flask at a rate of 1 drop per second; after the addition was completed, the reaction was stirred at room temperature for 6 h and monitored by thin layer chromatography until the reaction was complete.

[0074] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and a mixed solution of dichloromethane and methanol as eluent, and then the product is enriched and the product is made into 1 H NMR ( Figure 2 As shown), comonomer A is finally obtained.

[0075] Preparation of degradable polybiscyclopentadiene-based degradable thermosetting material in this embodiment:

[0076] (1) 0.15 parts of catalyst and 0.03 parts of inhibitor were dissolved in 96.82 parts of dicyclopentadiene;

[0077] (2) adding 3 parts of the synthesized monomer A to the mixed solution, and ultrasonically dispersing the vial containing the mixed solution in an ice water bath for 2 minutes to obtain a dispersion;

[0078] (3) The dispersion is then injected into a prefabricated mold, and after local thermal initiation at 200° C., polymerization is carried out through its own heat propagation to obtain a mechanically induced controllable degradation polydicyclopentadiene thermosetting material.

[0079] The structural formula of the mechanical force-induced controllable degradation polydicyclopentadiene thermosetting material is shown in Formula 5:

[0080]

[0081] Degradation performance test of polybiscyclopentadiene-based degradable thermosetting material in this example:

[0082] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ball milling for 2 h;

[0083] (2) In the second step, the ball-milled sample was immersed in a 0.1 M tetrabutylammonium fluoride / chloroform solution at room temperature (25°C) for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 60°C for 48 h. After constant weight was obtained, the remaining weight was weighed and recorded.

[0084] Embodiment 2 to Embodiment 4

[0085] The raw materials and formula of a polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of Examples 2 to 4 are shown in Table 1.

[0086] The preparation of the ladder-based cross-linked comonomer A containing a silicon ether unit and a force-sensitive unit and the polybiscyclopentadiene-based degradable thermosetting material and the degradation performance testing process are the same as in Example 1.

[0087] Example 5

[0088] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (ie, degradable PDCPD thermosetting material) of this embodiment are shown in Table 1.

[0089] The preparation of the ladder-based cross-linked comonomer A containing silyl ether units and force-sensitive units and the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0090] The degradation performance test process is as follows:

[0091] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ball milling for 2 h;

[0092] (2) In the second step, the ball-milled sample was immersed in a 0.1 M tetrabutylammonium fluoride / chloroform solution at 35°C for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 60°C for 48 h. After constant weight was achieved, the remaining weight was weighed and recorded.

[0093] Example 6

[0094] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (ie, degradable PDCPD thermosetting material) of this embodiment are shown in Table 1.

[0095] The preparation of the ladder-based cross-linked comonomer A containing silyl ether units and force-sensitive units and the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0096] The degradation performance test process is as follows:

[0097] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ball milling for 2 h;

[0098] (2) In the second step, the ball-milled sample was immersed in a 0.1 M tetrabutylammonium fluoride / chloroform solution at 45°C for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 60°C for 48 h. After constant weight was obtained, the remaining weight was weighed and recorded.

[0099] Example 7

[0100] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (ie, degradable PDCPD thermosetting material) of this embodiment are shown in Table 1.

[0101] The preparation of the ladder-based cross-linked comonomer A containing silyl ether units and force-sensitive units and the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0102] The degradation performance test process is as follows:

[0103] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ultrasonic treatment for 12 h;

[0104] (2) In the second step, the ultrasonically treated sample was immersed in a 0.1 M tetrabutylammonium fluoride / chloroform solution at 35°C for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 60°C for 48 h. After constant weight was achieved, the remaining weight was weighed and recorded.

[0105] Example 8

[0106] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (ie, degradable PDCPD thermosetting material) of this embodiment are shown in Table 1.

[0107] The preparation of the ladder-based cross-linked comonomer A containing silyl ether units and force-sensitive units and the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0108] The degradation performance test process is as follows:

[0109] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ball milling for 2 h;

[0110] (2) In the second step, the ball-milled sample was immersed in a 0.1 M hydrochloric acid / methanol solution at 35 °C for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 80 °C for 48 h. After constant weight was achieved, the remaining weight was weighed and recorded.

[0111] Example 9

[0112] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (ie, degradable PDCPD thermosetting material) of this embodiment are shown in Table 1.

[0113] The preparation of the ladder-based cross-linked comonomer A containing silyl ether units and force-sensitive units and the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0114] The degradation performance test process is as follows:

[0115] (1) In the first step, 1 g of controllably degradable thermosetting PDCPD material was taken at room temperature after ultrasonic treatment for 12 h;

[0116] (2) In the second step, the ball-milled sample was immersed in a 0.1 M hydrochloric acid / methanol solution at 35 °C for 12 h. After the immersion, the remaining solid was wiped clean with filter paper and placed in a vacuum oven at 80 °C for 48 h. After constant weight was achieved, the remaining weight was weighed and recorded.

[0117] Example 10

[0118] A polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this embodiment includes the following raw materials in parts by weight: 94.82 parts of dicyclopentadiene, 5 parts of ladder-based cross-linked copolymer monomer B containing silyl ether units and force-sensitive units, 0.15 parts of a catalyst, and 0.03 parts of an inhibitor (as shown in Table 1).

[0119] Among them, the structure of the ladder-based cross-linked copolymer monomer B containing a silyl ether unit and a force-sensitive unit is shown in Formula 6:

[0120]

[0121] Monomer B in this example (synthetic route is shown in Figure 3 ) preparation:

[0122] (1) In a three-necked flask containing 500 ml of dichloromethane, 0.2 mol (28.036 g) of bicyclo[2.2.0]hex-5-ene-2,3-dimethanol and 0.22 mol (14.982 g) of imidazole were added and stirred; then 0.1 mol (29.694 g) of 1,2-bis(trichloromethylsilyl)ethane was dissolved in 250 ml of dichloromethane, and the mixed solution was added dropwise to the three-necked flask at a rate of 1 drop per second; after the addition was completed, the reaction solution was stirred at room temperature for 2 h, and then the reaction was monitored by thin layer chromatography until the reaction was complete.

[0123] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and a mixed solution of dichloromethane and methanol as eluent, and then the product is enriched and the product is made into 1H NMR ( Figure 4 ), and finally obtain comonomer B.

[0124] The preparation process of the polybiscyclopentadiene-based degradable thermosetting material in this embodiment is the same as that in Example 1.

[0125] The structural formula of the mechanical force-induced controllable degradation polydicyclopentadiene thermosetting material is shown in Formula 7:

[0126]

[0127] The degradation performance test of the polybiscyclopentadiene-based degradable thermosetting material of this embodiment is the same as that of Example 5.

[0128] Embodiment 11

[0129] A polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this embodiment includes the following raw materials in parts by weight: 94.82 parts of dicyclopentadiene, 5 parts of ladder-based cross-linked copolymer monomer C containing silyl ether units and force-sensitive units, 0.15 parts of a catalyst, and 0.03 parts of an inhibitor (as shown in Table 1).

[0130] Among them, the structure of the ladder-based cross-linked copolymer monomer C containing a silyl ether unit and a force-sensitive unit is shown in Formula 8:

[0131]

[0132] Monomer C in this example (synthetic route is shown in Figure 5 ) preparation:

[0133] (1) In a three-necked flask containing 1 L of dichloromethane, 0.2 mol (28.036 g) of bicyclo[2.2.0]hex-5-ene-2,3-dimethanol and 0.22 mol (14.982 g) of imidazole were added and stirred; then 0.1 mol (22.805 g) of 1,2-dimethyl-1,1,2,2-tetrachlorodisilane was dissolved in 500 ml of dichloromethane, and the 1,2-dimethyl-1,1,2,2-tetrachlorodisilane / dichloromethane mixed solution was added dropwise to the three-necked flask at a rate of 2 drops per second; after the addition was completed, the reaction solution was stirred at room temperature for 4 h, and then the reaction was monitored by thin layer chromatography until the reaction was complete.

[0134] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and dichloromethane and methanol as eluents, and then the product is enriched and the product is made into 1 H NMR ( Figure 6 ), and finally obtain comonomer C.

[0135] The preparation process of the polybiscyclopentadiene-based degradable thermosetting material of this embodiment is the same as that of Embodiment 1.

[0136] The structural formula of the mechanical force-induced controllable degradation polydicyclopentadiene thermosetting material is shown in Formula 9:

[0137]

[0138] The degradation performance test of the polybiscyclopentadiene-based degradable thermosetting material in this example is the same as that in Example 5.

[0139] Comparative Example 1

[0140] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0141] The preparation of the polydicyclopentadiene-based degradable thermosetting material in this comparative example and the degradation performance testing process are the same as those in Example 5.

[0142] Comparative Example 2

[0143] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0144] The basic process and target structure of this comparative example are the same as those in Example 1, but the preparation method is different. The specific process is as follows:

[0145] (1) In a three-necked flask containing 200 ml of dichloromethane, 0.2 mol (28.036 g) of bicyclo[2.2.0]hex-5-ene-2,3-diethanol and 0.22 mol (47.135 g) of toluenesulfonic acid were added and stirred; then 0.1 mol (25.611 g) of 1,2-bis(methyldichlorosilyl)ethane was dissolved in 150 ml of dichloromethane, and the mixture was added dropwise to the three-necked flask at a rate of 1 drop per second; after the addition was completed, the reaction was stirred at room temperature for 30 min and monitored by thin layer chromatography until the reaction was complete.

[0146] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and a mixed solution of dichloromethane and methanol as eluent, and then the product is enriched and the product is made into 1 H NMR.

[0147] It was found that the reaction was not successful and the method could not produce comonomer A, so the subsequent material preparation was not carried out.

[0148] Comparative Example 3

[0149] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0150] The preparation of the polydicyclopentadiene-based degradable thermosetting material in this comparative example and the degradation performance testing process are the same as those in Example 5.

[0151] Comparative Example 4

[0152] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0153] The preparation process and degradation performance testing process of the polydicyclopentadiene-based degradable thermosetting material in this comparative example are the same as those in Example 5.

[0154] Comparative Example 5

[0155] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0156] The preparation process of the polybiscyclopentadiene-based degradable thermosetting material in this comparative example is the same as that in Example 1.

[0157] The degradation performance test of polybiscyclopentadiene-based degradable thermosetting materials is as follows:

[0158] At room temperature, 1 g of controllably degradable thermosetting PDCPD material was directly taken after ball milling for 2 h; the ball-milled sample was placed in a vacuum oven at 60 °C for 48 h, and the remaining weight was recorded after constant weight was obtained.

[0159] Comparative Example 6

[0160] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0161] The preparation process of the polybiscyclopentadiene-based degradable thermosetting material in this comparative example is the same as that in Example 1.

[0162] The degradation performance test of polybiscyclopentadiene-based degradable thermosetting materials is as follows:

[0163] Take 1g of controllable degradation thermosetting PDCPD material, soak the sample in 0.1M tetrabutylammonium fluoride / chloroform solution at 35°C for 12h. After soaking, wipe the remaining solid with filter paper, place it in a vacuum oven at 60°C for 48h, weigh it and record the remaining weight after constant weight.

[0164] Comparative Example 7

[0165] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0166] The structural formula of the monomer D containing the silyl ether moiety, cyclobutene and anhydrous sensitization moiety is shown in Formula 10:

[0167]

[0168] Monomer D (synthetic route see Figure 7 ) preparation:

[0169] (1) 0.2 mol (28.440 g) of 3-cyclobutene-1,2-dimethanol and 0.22 mol (14.982 g) of imidazole were added to a three-necked flask containing 200 ml of dichloromethane and stirred; then 0.1 mol (25.611 g) of 1,2-bis(dichloromethylsilyl)ethane was dissolved in 150 ml of dichloromethane, and the mixture was added dropwise to the three-necked flask at a rate of 1 drop per second; after the addition was completed, the reaction was stirred at room temperature for 30 min and monitored by thin layer chromatography until the reaction was complete.

[0170] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and a mixed solution of dichloromethane and methanol as eluent, and then the product is enriched and the product is made into 1 H NMR ( Figure 8 ), and finally obtain comonomer D.

[0171] The preparation process of the polydicyclopentadiene-based degradable thermosetting material and the degradation performance testing process of this comparative example are the same as those of Example 5.

[0172] Comparative Example 8

[0173] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0174] Among them, the structural formula of the monomer E containing the force-sensitive unit and cyclobutene and the silicon-free ether unit is shown in Formula 11:

[0175]

[0176] The preparation process of the polydicyclopentadiene-based degradable thermosetting material and the degradation performance testing process of this comparative example are the same as those of Example 5.

[0177] Comparative Example 9

[0178] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0179] The structural formula of the monomer F without silyl ether moiety, force-sensitive moiety and cyclobutene is shown in Formula 12:

[0180]

[0181] The preparation process of the polydicyclopentadiene-based degradable thermosetting material and the degradation performance testing process of this comparative example are the same as those of Example 5.

[0182] Comparative Example 10

[0183] The raw materials and formula of the polydicyclopentadiene-based degradable thermosetting material (i.e., degradable PDCPD thermosetting material) of this comparative example are shown in Table 2.

[0184] The structural formula of the monomer G containing a silyl ether moiety, an insensitivity moiety and cyclobutene is shown in Formula 13:

[0185]

[0186] Monomer G (synthetic route see Fig. 9 ) preparation:

[0187] (1) In a three-necked flask containing 200 ml of dichloromethane, 0.2 mol (24.836 g) of 5-norbornene-2-methanol and 0.22 mol (14.982 g) of imidazole were added and stirred; then 0.1 mol (20.124 g) of chloro-[(chloro-dimethyl-silyl)methyl]-dimethyl-silane was dissolved in 150 ml of dichloromethane, and the mixture was added dropwise to the three-necked flask at a rate of 1 drop per second; after the addition was completed, the reaction was stirred at room temperature for 30 min and monitored by thin layer chromatography until the reaction was complete.

[0188] (2) After the reaction is completed, the reaction product is crudely treated by extraction, and the organic phase is further subjected to rapid column chromatography using neutral alumina as filler and a mixed solution of dichloromethane and methanol as eluent, and then the product is enriched and the product is made into 1 H NMR ( Fig.10 ), and finally obtain comonomer G.

[0189] The preparation process of the polydicyclopentadiene-based degradable thermosetting material and the degradation performance testing process of this comparative example are the same as those of Example 5.

[0190] Tests and Results

[0191] The materials prepared in the above embodiments and comparative examples were cut to prepare test specimens, and the test method was as follows:

[0192] Tensile strength: tested according to ISO 527-2:1993 standard, speed is 50mm / min;

[0193] Elongation at break: Tested according to ISO 527-2:1993 standard, speed is 50mm / min;

[0194] Heat of polymerization: The heat of polymerization H r of the sample was measured by DSC under N2 atmosphere. About 10 mg of the prepared dicyclopentadiene mixture was added to the crucible, and the sample was cooled to -10 °C at a rate of 5 °C per minute, kept constant for 2 minutes, and then raised to 200 °C at a rate of 5 °C per minute. After baseline calibration, the heat flow between 20 °C and 150 °C was integrated with respect to temperature to calculate the heat of polymerization H r.

[0195] Degree of curing: In N2 atmosphere, the residual heat of reaction H res is first measured by DSC. Take about 10 mg of the cured sample and perform a hot-cold-hot cycle at a rate of 10°C per minute at -50°C and 250°C. After baseline calibration, the heat flow between 50°C and 150°C is integrated with the temperature to calculate the residual heat of reaction H res. The degree of curing α is calculated by the following formula:

[0196]

[0197] The molecular weight between cross-linking points Mc: Mc is calculated according to the following formula:

[0198]

[0199] In the formula, the value of ρ is 1g·cm -3 , R is the ideal gas constant, which is 8.314 J·mol -1 ·K -1 ,T is T g +50K, E′ Tg+50K The temperature is T g Storage modulus of the sample at +50K.

[0200] Thermal decomposition temperature: weigh about 10 mg of sample, in a N2 environment, starting from room temperature, and heating to 800°C at a rate of 10°C per minute.

[0201] Degradation performance:

[0202] (1) In the first step, the degradation properties of thermosetting PDCPD materials are activated under the action of mechanical force;

[0203] (2) In the second step, the sample prepared in the first step is immersed in a mixture of an acid or alkaline solution and a solvent at room temperature or under heating conditions. Under stirring conditions, the thermosetting PDCPD material is degraded into soluble oligomer fragments.

[0204] The results are shown in Tables 3, 4, 5 and 6.

[0205] Table 3 Mechanical properties of polydicyclopentadiene-based degradable thermosetting materials in various examples

[0206]

[0207]

[0208] Table 4 Degradation performance indexes of polydicyclopentadiene-based degradable thermosetting materials in various examples

[0209]

[0210] Table 5 Mechanical properties of polydicyclopentadiene-based degradable thermosetting materials in various comparative examples

[0211]

[0212]

[0213] Table 6 Degradation performance indicators of polydicyclopentadiene-based degradable thermosetting materials in various proportions

[0214]

[0215] Among them, Table 1 and Table 2 are the experimental formulas of Examples 1 to 11 and Comparative Examples 1 to 10, Table 3 and Table 5 are the thermal properties and mechanical properties data of the mechanical force induced controllable degradation polydicyclopentadiene-based degradable thermosetting materials prepared by Examples 1 to 11 and Comparative Examples 1 to 10, and Table 4 and Table 6 are the degradation performance data of the mechanical force induced controllable degradation polydicyclopentadiene-based degradable thermosetting materials prepared by Examples 1 to 11 and Comparative Examples 1 to 10.

[0216] The mechanical property data of Examples 1 to 11 in Table 3 show that the introduction of ladder-based crosslinked comonomers containing silicon ether moieties and force-sensitive moieties increases the tensile strength of the polydicyclopentadiene material with the increase of the comonomer content, and the elongation at break decreases with the increase of the comonomer content, because the increase of the comonomer content leads to an increase in the crosslinking degree of the material. The polymerization heat and curing degree of the polydicyclopentadiene material increase with the increase of the introduction amount of ladder-based crosslinked comonomers containing silicon ether moieties and force-sensitive moieties, because the ring tension of the cyclobutene introduced into the ladder-based structure is large, and the heat released by the fracture is large, the polymerization heat increases accordingly, and the curing degree increases accordingly. As the amount of ladder-based cross-linking copolymer monomers containing silyl ether units and force-sensitive units increases, the glass transition temperature increases and the molecular weight between cross-linking points decreases; because the introduction of monomers increases the cross-linking point density, the free volume of the polymer decreases, the degree to which the activity of the molecular chain is constrained also increases, the average chain length between adjacent cross-linking points decreases, and the molecular weight between the cross-linking points decreases, which hinders the movement of molecular chain segments and increases the glass transition temperature. At the same time, the initial decomposition temperature and maximum decomposition temperature of the material increase.

[0217] The degradation performance data in Table 4 show that the polydicyclopentadiene materials containing ladder-based cross-linked comonomers with silane ether motifs and force-sensitive motifs are all degradable, and as the monomer content increases, the time required for degradation becomes shorter and the degradation efficiency becomes higher. However, chemical stimulation of different types of mechanical forces and different reagents has little effect on the degradation efficiency of the material, indicating that the material has excellent degradation performance. It can also be seen from the data that the comonomer can give PDCPD a degradation efficiency of over 98% at a low load (less than 3wt%), and when the comonomer load is 5wt%, the material can be completely degraded within 2 hours. There is no obvious increase in performance with the increase in monomer content, so 5wt% is the most suitable dose.

[0218] The relevant data results of Comparative Examples 1 to 10 in Tables 5 and 6 show that: in Comparative Example 1, the polydicyclopentadiene material without adding ladder-based crosslinked comonomers containing silane ether units and force-sensitive units has stable mechanical properties and cannot be degraded under mechanical ball milling and dilute hydrochloric acid stimulation under 45°C heating conditions; in Comparative Examples 3 and 4, ladder-based crosslinked comonomers containing silane ether units and force-sensitive units that are not within the scope of the formula authority requirements are added. When the monomer content in the polydicyclopentadiene material is too little, it cannot be completely degraded. When the monomer content is too much, although it can be degraded, the tensile strength of the material reaches 80.9MPa, and the elongation at break is only The ratio of the polydicyclopentadiene monomer to the polydicyclopentadiene monomer is 5.1%, and the brittleness of the material increases, which is not conducive to its comprehensive mechanical properties; Comparative Examples 5 and 6 are tested by changing the degradation method, and the results show that the degradation of the material cannot be achieved by only physical mechanical force or only chemical stimulation; Comparative Example 7 only introduces monomers containing silicon ether structure, Comparative Example 8 only introduces ladder ene monomers containing force-sensitive groups, and Comparative Example 9 introduces ladder ene cross-linked copolymer monomers without silicon ether units and force-sensitive units. The results show that the mechanical properties of the polydicyclopentadiene material containing one of the groups or neither of the two groups are significantly reduced, and the material cannot be degraded. Among them, Comparative Example 8 only contains ladder ene structure monomers, and the material is force-induced ring opening and bond breaking into fragments of different sizes during ball milling, but the material cannot be degraded under chemical stimulation. The mechanical properties and degradation properties of the polydicyclopentadiene material obtained above are significantly worse than those in the embodiment.

[0219] In summary, the introduction of the ladder-based cross-linked comonomer containing silyl ether units and force-sensitive units in the present invention gives the polydicyclopentadiene thermosetting material degradation properties while having good strength and thermal stability, and gives the material good toughness, which has good application prospects.

[0220] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ladder olefin-based crosslinking comonomer, characterized in that: It is a ladder-based cross-linked copolymer monomer containing a silicon ether unit and a force-sensitive unit, and its structural formula is shown in Formula 1: In the formula, R1 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 sulfur heterocyclic group; R2 is selected from one or more of a direct bond, a methylene group, a 1,2-ethylene group, a 1,3-propylene group, a 1,4-butylene group, a methyleneoxycarbonyl group, an ethyleneoxycarbonyl group, a methacryl group, a methyleneoxy group, an ethyleneoxy group, and a propyleneoxy group; R3 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 Sulfur heterocyclic group.

2. The ladder olefin-based crosslinking comonomer according to claim 1, characterized in that: R1 is selected from C 1-6 Alkyl, halogenated; R2 is selected from direct bond, methylene, 1,2-ethylene; R3 is selected from C 1-6 Alkyl, halo.

3. A method for preparing a ladder olefin-based crosslinking comonomer as claimed in claim 1, characterized in that: It is synthesized by the reaction of ladder olefin diol and dichlorosilane, and the reaction equation is shown in Formula 2: First, dissolve ladder olefin diol and catalyst in an organic solvent, and lower the temperature to below 0°C, add dichlorosilane dropwise to the above solution, and react and stir at 0-100°C for 4-48 hours; after the reaction, wash, separate and dry to obtain a ladder olefin cross-linking copolymer containing a silyl ether unit and a force-sensitive unit; Wherein, the catalyst is one of imidazole, 1-methylimidazole, 2-methylimidazole, benzimidazole, monoethanolamine, diethanolamine, diisopropanolamine, N-methyldiethanolamine, triethylamine, triethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, pyridine, 4-pyrrolidinopyridine, 4-N,N-dimethylpyridine, and 4-dimethylaminopyridine.

4. The method for preparing the ladder olefin-based cross-linked comonomer according to claim 3, characterized in that: The organic solvent is one or more of benzene, toluene, xylene, isopropyl benzene, isopentane, n-pentane, cyclopentane, n-hexane, cyclohexane, cyclohexanone, toluenecyclohexanone, methylcyclohexane, heptane, n-octane, isooctane, dichloromethane, 1,2-dichloroethane, chloroform, trichloroethane, carbon tetrachloride, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl formate, isobutyl acetate, propyl acetate, ethyl ether, petroleum ether, isopropyl ether, methyl tert-butyl ether, anisole, tributyl methyl ether, propylene oxide, dioxane, tetrahydrofuran, dioxane, methyl ethyl ketone, acetone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methanol, ethanol, and isopropanol.

5. A degradable PDCPD thermosetting material, characterized in that: Prepared by polymerization reaction of the ladder-based cross-linked comonomer according to claim 1 and dicyclopentadiene, the structural formula is shown in Formula 3: Wherein, x, y, z, m, n, and p are all integers between 5 and 100; At the same time, R1 is selected from hydrogen atoms, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 sulfur heterocyclic group; R2 is selected from one or more of a direct bond, a methylene group, a 1,2-ethylene group, a 1,3-propylene group, a 1,4-butylene group, a methyleneoxycarbonyl group, an ethyleneoxycarbonyl group, a methacryl group, a methyleneoxy group, an ethyleneoxy group, and a propyleneoxy group; R3 is selected from hydrogen atom, C 1-20 Alkyl, C 2-20 Olefin group, C 2-20 Alkyne, C 6-20 Aromatic hydrocarbon, carboxyl, C 1-20 Hydrocarbonyl, haloformyl, hydroxyl, amino, nitro, nitroso, carbamoyl, cyano, formyl, C 1-20 Alkyloxy, halo, C 3-20 Oxyheterocyclic group, C 3-20 Nitrogen heterocyclic group, C 3-20 Phosphorus heterocyclic group, C 3-20 Sulfur heterocyclic group.

6. The degradable PDCPD thermosetting material according to claim 5, characterized in that: R1 is selected from C 1-6 Alkyl, halogenated; R2 is selected from direct bond, methylene, 1,2-ethylene; R3 is selected from C 1-6 Alkyl, halo.

7. The degradable PDCPD thermosetting material according to claim 5, characterized in that: The preparation of the degradable PDCPD thermosetting material includes the following raw materials in parts by weight:

8. A method for preparing a degradable PDCPD thermosetting material according to any one of claims 5 to 7, characterized in that: It is synthesized by front-end ring-opening metathesis polymerization of dicyclopentadiene and ladder-based cross-linked copolymers in the presence of a ruthenium catalyst and a phosphate inhibitor.

9. A method for degrading a degradable PDCPD thermosetting material according to any one of claims 5 to 7, characterized in that: Here are the steps: (1) Activate the degradation properties of PDCPD thermosetting materials under mechanical force; (2) Immersing the sample prepared in step (1) in a mixture of an acid solution or an alkaline solution and a solvent at room temperature or under heating conditions; degrading the PDCPD thermosetting material into soluble oligomer fragments under stirring conditions.

10. The method for degrading a degradable PDCPD thermosetting material according to claim 9, characterized in that: The mechanical force is in the form of one or more of ultrasound, mechanical vibration, ball milling, grinding, impact, calendering, crushing, shearing, stretching, torsion, and bending; The acid in the acid solution is one or more of hydrochloric acid, hydrobromic acid, hydrofluoric acid, hydrocyanic acid, hydrosulfuric acid, nitric acid, sulfuric acid, sulfurous acid, acetic acid, acetic acid, trifluoroacetic acid, trichloroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, lactic acid, formic acid, propionic acid, citric acid, sulfurous acid, phosphoric acid, benzoic acid, maleic acid, phthalic acid, hypochlorous acid, chloric acid, chlorous acid, and perchloric acid; The alkali in the alkali solution is one or more of tetrabutylammonium fluoride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetrabutylammonium chloride, tetramethylammonium fluoride, tetramethylammonium chloride, tetramethylammonium bromide, tetramethylammonium iodide, tetraethylammonium fluoride, tetraethylammonium chloride, tetraethylammonium bromide, tetraethylammonium iodide, tetrapropylammonium fluoride, tetrapropylammonium chloride, tetrapropylammonium bromide, tetrapropylammonium iodide, tributylmethylammonium fluoride, and tetraoctylammonium fluoride; The solvent is one or more of water, n-pentane, isopentane, cyclopentane, hexane, cyclohexane, heptane, benzene, toluene, xylene, chlorobenzene, isopropylbenzene, dichloromethane, 1,2-dichloroethane, chloroform, trichloroethane, carbon tetrachloride, methanol, ethanol, ethylene glycol, propanol, isopropanol, butanol, isobutyl alcohol, tert-butyl alcohol, amyl alcohol, benzyl alcohol, ethyl acetate, ethyl formate, isobutyl acetate, methyl acetate, ether, petroleum ether, isopropyl ether, methyl tert-butyl ether, tetrahydrofuran, dioxane, methyl ethyl ketone, acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide; Meanwhile, the molar concentration of the acid or alkali in the mixture of the acid solution or alkali solution and the solvent is 0.01 to 100 mol / L; The heating conditions are: heating temperature 0°C to 100°C, and heating time 1 to 100 hours.

Citation Information

Patent Citations

  • Synthetic method of degradable polystyrene based on nitrobenzyl disulfide and pyridinium ester block macromolecular chain transfer agent

    CN115028760A

  • Degradable polydicyclopentadiene thermosetting material containing silyl ether element and preparation method of degradable polydicyclopentadiene thermosetting material

    CN117343235A

  • Force-sensitive acetal monomer containing ladder ene structure and degradable thermosetting polydicyclopentadiene material

    CN117362266A